The making of religion: An essay on the definition of ‘African religion’ through the cases of the Yorùbá and Candomblé - Ferreira Dias, J. (Journal of Religion in Africa, 2022)
This essay aims to focus on the concept of religion and its conceptual implications in the observation of African religions, taking the Yorùbá and Candomblé religious attitudes and beliefs as case studies. I intend to trace a new itinerary in the conceptualization of African religious experiences, using native structures as the setting for theory. I point out that African-Yorùbá religious experience is deeply merged with ritual practice – religion is made – and tied to a sense of origins and duties that must be fulfilled. In that vein, I present alternative categories to the classic ones of monotheism, polytheism, and pantheon.